Índices prognósticos e desfechos clínicos de pacientes em unidades de terapia intensiva da região não metropolitana em Sergipe - Teixeira, Rosane Milet Passos (2021)
Introduction: The Intensive Care Unit (ICU) is an environment for seriously ill patients. Prognosis scores are widely used to guide the team's decision making, when assessing patients' clinical conditions and prognosis. Studies have investigated the use of scores, in order to subsidize their impact on therapeutic effectiveness and clinical outcomes. However, there is a dearth of studies that have carried out such an investigation. Objective: To assess clinical outcomes, describe the severity profile, compare outcomes between ICUs and assess the survival of patients admitted to intensive care units in the non-metropolitan region of Sergipe. Method: Prospective cohort study, carried out between 2018 and 2019. Patients admitted to the only two ICUs in the non-metropolitan region of the State of Sergipe, aged 18 years or over, who had a minimum stay of 24 hours were included. For data collection, the Simplified Acute Physiology Score (SAPS III), Sequential Organ Failure Assessment (SOFA) and Nursing Activities Score (NAS) scores were used and a questionnaire was applied for the clinical and demographic characterization of patients. For data analysis, a significance level of 5% was adopted and absolute frequency and relative percentage were used to describe categorical variables; mean, median, standard deviation and interquartile range to describe continuous variables. Fisher's Exact, Pearson's Chi-Square and Pearson's Chi-Square tests with Monte- Carlo simulations were applied to assess the association between categorical variables. The Shapiro-Wilks test was used to assess the adherence of continuous variables to normal distribution, the Mann-Whitney test to assess differences in measures of central tendency; linear regression to analyze continuous variables and logistic regression for binary and multinomials in confounding models. The research was approved by the Research Ethics Committee of the Federal University of Sergipe. Results: Data from 219 patients were included, 53.9% were from Hospital Regional de Itabaiana (HRI) and 46.1% from Hospital Universitário de Lagarto (HUL). The SAPS III values (B = 8.22; p = 0.001), death (OR = 3.14; p <0.001), dialysis (OR = 2.98, p = 0.032), pressure injury (OR = 14, 0; p <0.01), infection (RC = 2.46; p = 0.003), length of stay in the intensive care unit (B = 1.32; p = 0.045) and length of hospital stay (B = 2 , 11; p <0.001) were higher at the Hospital Universitário de Lagarto (HUL). The survival curve for length of stay in the ICU indicated that patients had shorter length of stay, with a higher survival rate and lower mortality in the HRI. Conclusion: The patients seen at the HUL, in addition to having more comorbidities, also needed greater support on admission, which increased the number of unfavorable outcomes.